1999
DOI: 10.1192/pb.23.8.493
|View full text |Cite
|
Sign up to set email alerts
|

Higher psychiatric trainees and the Caiman reforms

Abstract: Aimsand method The specialistregistrar(SpR)grade was introduced in 1996,taking the place of the senior registrar (SR) grade. We surveyed higher trainees in Scotland in order to draw comparisons between the two grades and assesssatisfaction with the changes. A postal questionnaire was sent to all higher trainees (n=129) in Scotland seeking information on structure of training, work patterns and views. Results Sixty-twoper cent of traineesresponded.There was little difference in the activity and structure of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…It is encouraging that the majority of Scottish trainees in psychiatry (66%) were able to protect the allocated time for research, although this figure is lower than that found previously (78%) in Scotland by Cavanagh & Haut (1999).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…It is encouraging that the majority of Scottish trainees in psychiatry (66%) were able to protect the allocated time for research, although this figure is lower than that found previously (78%) in Scotland by Cavanagh & Haut (1999).…”
Section: Discussioncontrasting
confidence: 47%
“…However, more recent surveys suggest that problems with research training remain common. Cavanagh & Haut (1999) examined the transition from senior registrar to specialist registrar grade in Scotland, and found that 22% of SpRs in psychiatry were unable to take two research sessions per week as compared with 12% of senior registrars.…”
Section: Discussionmentioning
confidence: 99%